Design and development of a comeback CanSat - Sunil, Navnita (2017)
CanSat is an educational tool used to inspire students to pursue the field of Satellite Technology. It is a scaled down version of a satellite, and like a satellite it also has a communication subsystem, a structural subsystem, a telemetry subsystem and a power subsystem. The design and development of a CanSats largely depends on their specific missions. Telemetry CanSats collect information like temperature, pressure and altitude and send it to the ground station. A Comeback CanSat aims at landing in a predetermined location after the launch using autonomous navigation capabilities. This project aims at building a Comeback CanSat on the Arduino platform. It autonomously navigates itself to a particular destination by making use of a Global Positioning System Module and an Inertial Measurement Unit Board. Its flight would be steered and controlled using servo motors and a paraglide that are attached to the CanSat. The mechanical structure of the CanSat is a 3D printed model made of a thermoplastic called Poly Lactic Acid. In addition to this, the data calculated by the CanSat would be sent to the ground station via the Zigbee protocol. XBee modules are used as the communication system. The 2D testing that was conducted to determine the viability of the CanSat was successful. Future work can aim for a 3D testing, provided there is availability of a proper launching vehicle.